Patient-reported experiences during and following treatment with belantamab mafodotin for relapsed/refractory multiple myeloma in the DREAMM-2 study - Cardellino, Anna; Correll, Julia R.; Martin, Mona; Gorsh, Boris; Sapra, Sandhya; Popat, Rakesh (Frontiers in Oncology, 2023)
Introduction: Patients with relapsed or refractory multiple myeloma (RRMM) are likely to be living with persistent symptoms, especially bone pain and fatigue, and experiencing restrictions in their physical and social functioning, which reduce health-related quality of life.Methods: This qualitative interview study evaluated patients' perspectives about living with RRMM and their treatment with belantamab mafodotin, using interviews embedded in the Phase II DREAMM-2 trial (NCT03525678) with belantamab mafodotin. Patients consented to participate in up to 2 recorded telephone interviews (at treatment cycle 4 [C4] and at end of treatment [EOT]) comprising open-ended questions.Results: A total of 142 interviews were conducted with 111 unique patients. At C4, common symptoms included neuropathy, fatigue, and bone or joint pain. Improvements in symptom severity were reported by patients who responded to belantamab mafodotin. Symptoms associated with visual impairment, eye irritation, and eye pain reported during the trial were reported to be at-or near-resolution by the EOT interview. Regarding impacts of underlying MM, patients most commonly expressed concerns about changes in daily performance and lifestyle for both responders (67.5% of all impact expressions) and non-responders (63.2%). Overall, interview participants reported being satisfied with belantamab mafodotin treatment.Discussion: This qualitative patient interview study provides valuable insight into patients' symptomatic experience with belantamab mafodotin for their RRMM treatment and may help healthcare providers better anticipate their patients' real-world experience and needs when prescribing this novel agent in the clinic.